1994
DOI: 10.1122/1.550603
|View full text |Cite
|
Sign up to set email alerts
|

Modeling polymer melt‐flow instabilities

Abstract: SynopsisThe long-standing problem of polymer melt-flow instabilities is looked upon from a new and quite general mathematical viewpoint. A single mathematical model is developed allowing the macroscopic description of measurable state variables characterizing the different melt-flow instability regimes. Based on the theory of relaxation oscillations,a set of two coupled first-order ordinary differential equations, relating state variables-pressure and flow rate-provides sufficient degrees of freedom to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…In agreement with what described in literature [1][2][3][4][5], the oscillating flow that took place when such a type of instability occurred was characterized by evident fluctuations both in the pressure signal acquired in the reservoir of the rheometer and in the extrudate flow rate; the extrudate appearance was characterized by the alternation of relatively smooth and rough segments. An example of a pressure, P, vs time trace acquired during the oscillating flow exhibited by the HDPE here examined is shown in Figure 1.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In agreement with what described in literature [1][2][3][4][5], the oscillating flow that took place when such a type of instability occurred was characterized by evident fluctuations both in the pressure signal acquired in the reservoir of the rheometer and in the extrudate flow rate; the extrudate appearance was characterized by the alternation of relatively smooth and rough segments. An example of a pressure, P, vs time trace acquired during the oscillating flow exhibited by the HDPE here examined is shown in Figure 1.…”
Section: Resultssupporting
confidence: 86%
“…Instability phenomena in capillary flow have been the subject of many theoretical and experimental studies since the beginning of polymer science, but still receive considerable attention because of the limits they impose on die forming processes of polymers (some of the most relevant literature works are cited in the reference list [1][2][3][4][5]). These instabilities, which are commonly referred to as "melt fracture", produce irregularities and distortions at the extrudate surface and thus limit the industrial production rates and the technological opportunities of several polymers.…”
Section: Introductionmentioning
confidence: 99%
“…While it is clear that stress concentrations are a crucial factor for the development of the sharkskin instability, they cannot be the only factor. Issues that may also be involved include melt strength [12], the level of wall slip [20], the stability of the partial slip boundary condition [25] and the stability of the point of separation of the melt from the die exit [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Molenaar and Koopmans [25] proposed a local mechanism of stick-slip or relaxation oscillations in a thin peripheral layer near the die exit, similar to the oscillating defect observed at higher stresses. They modelled melt flow instabilities in terms of cyclic relaxation oscillations, during which potential energy is successively stored and relaxed, and found that above a critical wall shear stress, the increase in the flow curve becomes non-monotonic and successive stick-slip oscillations develop within a localised area at the die exit.…”
Section: Slip Mechanismsmentioning
confidence: 91%
“…Another peculiar effect, not yet mentioned, that is observed in experiments as well as in industrial circumstances, is the occurrence of the so-called 'shark-skin' instabilities at the surface of an extrudate (d. [10]). These shark-skins occur in extrusion processes before spurt turns up.…”
Section: Discussionmentioning
confidence: 99%